2010
DOI: 10.1021/la100458j
|View full text |Cite
|
Sign up to set email alerts
|

Light-Triggered Reversible Phase Transfer of Composite Colloids

Abstract: Composite colloids were prepared via grafting optically responsive spiropyran polymer brushes onto silica colloids. Similar to spiropyran, the polymer brushes undergo a reversible inversion from a hydrophobic state to a hydrophilic state upon irradiation with UV light (or vice versa by visible light). The composite colloids can thus reversibly transfer between oil and water phases, and this can be remotely triggered using light. At intermediate stages of irradiation, both hydrophobic and hydrophilic components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 52 publications
0
60
0
Order By: Relevance
“…[15] These distinct properties are the reason fort he extensive applications of spiropyrans in supramolecular complexes, [16][17][18][19][20][21][22][23][24][25] nanoparticle functionalization, [22][23][24][25] smart polymer materials, [26][27][28][29] nanocarriers, [31][32][33][34][35][36][37] and biochemical systems. The ring-opening causesc hargeaseparation,whichi nduces al arge dipolem omenti nM C. At the same time, this process is accompanied by as ubstantial structural change, which is not only spatial but also electronic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…[15] These distinct properties are the reason fort he extensive applications of spiropyrans in supramolecular complexes, [16][17][18][19][20][21][22][23][24][25] nanoparticle functionalization, [22][23][24][25] smart polymer materials, [26][27][28][29] nanocarriers, [31][32][33][34][35][36][37] and biochemical systems. The ring-opening causesc hargeaseparation,whichi nduces al arge dipolem omenti nM C. At the same time, this process is accompanied by as ubstantial structural change, which is not only spatial but also electronic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wu et al demonstrated reversible transport of silica nanoparticles grafted with optically responsive spiropyran polymer brushes between toluene and water. 215 In this system, the polymer brushes undergo a reversible inversion from a hydrophobic state to a hydrophilic state upon irradiation with UV light. This allowed the authors to also demonstrate that these particles can stabilise both O/W and W/O emulsions depending on the light environment they are subjected to.…”
Section: ) Drivers For the Choice Of Polymerization Methodsmentioning
confidence: 99%
“…4(B)], the regulation of the particle transport between immiscible liquids across the interface and the fabrication of ultrahydrophobic coatings with textured surfaces from aqueous dispersion. On the other hand, light‐responsive hairy colloids were prepared by Wu et al via grafting optically responsive spiropyran polymer brushes onto silica colloids 95. Polyspyropyran brushes undergo a reversible change from a hydrophobic state to a hydrophilic state upon irradiation with UV light (or vice versa by visible light).…”
Section: Practical Applications Of Polymer Brushesmentioning
confidence: 99%